Hubungan antara Kualiti Perkhidmatan dan Kecenderungan Pembelian Berulang oleh Pelanggan dalam Sektor Pengangkutan Penerbangan di Malaysia - Nurul Aimi Abdul Rahman; Fazian Hashim (Research in Management of Technology and Business, 2024)
Since the 1980s, the aviation sector in Malaysia has experienced rapid development. The competition within the air transportation sector has become increasingly intense, with numerous companies constantly attracting potential customers rigorously. This study aims to determine the relationship between service quality and repeat purchase intention by customers within the air transportation sector in Malaysia. The SERVQUAL model is employed in this study to assess the level of service quality based on five dimensions: tangibles, reliability, empathy, assurance, and responsiveness. The study focuses on users with a sample size of 384 respondents who are passengers utilizing air transportation at Senai International Airport, Johor Bahru, Malaysia. This study uses a quantitative method, an online questionnaire distributed to respondents. The result of the study shows that all objectives and hypotheses have been achieved and accepted. There is a significant correlation between the dimensions of service quality and the repeat purchase intention. Suggested improvements for future studies are sample sizes that include a larger population to obtain more meaningful and representative data.